Quantitative relationship between body weight gain in adulthood and incident type 2 diabetes: a meta‐analysis. Issue 3 (25th October 2013) - Kodama, S.; Horikawa, C.; Fujihara, K.; Yoshizawa, S.; Yachi, Y.; Tanaka, S.; Ohara, N.; Matsunaga, S.; Yamada, T.; Hanyu, O.; Sone, H.
Summary This meta‐analysis quantified the risk of type 2 diabetes mellitus (T2DM) preceded by body weight (BW) gain in the general population. Systematic literature searches retrieved 15 eligible studies. The BW gain was divided into early weight‐gain, which was defined as BW gain from early adulthood (18–24 years of age) to cohort entry (≥25 years of age), and late weight‐gain, which was defined as BW gain from cohort entry. The pooled relative risk (RR; 95% confidence interval [CI]) of T2DM for an increment of BW gain standardized into a 5‐kg m−2 increment in the body mass index (BMI) was 3.07 (2.49–2.79) for early weight‐gain and 2.12 (1.74–2.58) for late weight‐gain. When limiting analysis to studies that concurrently examined T2DM risk for current BMI (defined in both groups as BMI at cohort entry), a larger magnitude of T2DM risk was revealed for early weight‐gain compared with current BMI (RR [95% CI], 3.38 [2.20–5.18] vs. 2.39 [1.58–3.62]), while there was little difference between late weight‐gain (RR [95% CI], 2.21 [1.91–2.56]) and current BMI (RR [95% CI], 2.47 [1.97–3.30]). The meta‐analysis suggested that BW gain was a quantifiable predictor of T2DM, as well as current obesity in adults. Particularly, BW gain in early rather than middle‐to‐late adulthood played an important role in developing T2DM.